Development of the External Factors Evaluation Matrix Based on Scenario Planning (Case Study: Iran’s Sports Industry) - FarokhShahinia, Reza; Shirvani Naghani, Moslem; Pourkazemi, Mahdi (Journal of Foresight and Health Governance, 2025)
Appropriate organizational responses to environmental variables have oriented strategic planning toward novel approaches such as strategic foresight. The purpose of this study is the qualitative development of the External Factors Evaluation (EFE) Matrix affecting Iran’s sports industry using scenario planning. This research is developmental–applied in terms of purpose, mixed-method in nature, and follows a survey path incorporating cross-impact analysis and scenario planning. The statistical population included associate professors and full professors in the field of sports management, selected through a mixed sampling method in four phases. The results indicated that, based on different states of key uncertainties in the Scenario Wizard software, four feasible scenarios with high internal consistency were identified. Based on the occurrence probabilities of their various assumptions, the EFE matrix can be developed. Therefore, the proposed matrix of this study can assist in formulating more resilient strategies in the uncertain environment of Iran's sports industry by enabling more precise identification and evaluation of external factors. The innovation of the present research lies in integrating the EFE matrix—as one of the most important tools in strategic management—with scenario planning, one of the most significant methods in futures studies. Hence, the use of the evolved EFE matrix extracted from this research is recommended not only for managers of organizations active in the sports industry but also for long-term planners in other sectors and organizations.